Antioxidant Therapy in Nonalcoholic Steatohepatitis. (22nd November 2012) - Al-Busafi, Said A.; Bhat, Mamatha; Wong, Philip; Ghali, Peter; Deschenes, Marc
Abstract : Nonalcoholic steatohepatitis (NASH) affects up to 3% of the North American population. It occurs as a manifestation of the insulin-resistant state and oxidative stress is thought to be a key component of its pathophysiology. Exercise and diet, which are the mainstay of therapy, are difficult to achieve and maintain with a disappointing long-term compliance record. There is growing literature on the potential for antioxidant therapy. The recent literature strongly suggests that vitamin E supplementation and other putative free radical scavengers and/or antioxidants are beneficial in improving biochemical and histological parameters in NASH.